Fluffy bunnies 2 : the Schnoz of Doom - Beaty, Andrea (Amulet Books, 2015)
Film-loving twins Joules and Kevin face new evil bunnies from outer space when odorous extraterrestrials that use "smellepathy" to control their prey's brain arrive to conquer the world.